European Calvinism: history, providence, and martyrdom - Pettegree, Andrew (Studies in church history, 1997)
For students of the Reformation one of the main conceptual problems is undoubtedly the distance between the mind-set of our age and theirs. We look at the Reformation as a new beginning, the moment when the Church fragmented into competing Churches, and one of the fundamental developments of the Early Modern Age: a term which in itself presents a view of progress and change as one of the determining characteristics of the age.Contemporaries, however, had a very different perception; they saw the movement for evangelical reform as one of renovation and renewal. They believed that they were attempting to recover what was best in the past of the Church, which had since become hopelessly corrupted. With others of their contemporaries they despised innovation. One can surely only understand Martin Luther if one recognizes the depth of his conservatism; that his personal crusade was to a large extent fuelled by a sense of moral outrage and indignation at what the papacy had done to his Church.